2018
DOI: 10.14704/nq.2018.16.6.1314
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Effectiveness of Snyder's Theory-Based Group Hope Therapy to Improve Self-Efficacy of University Students in Finance

Abstract: Self-efficacy as a motivating factor leads to increased academic performance and stress reduction. Therefore, training to improve academic self-efficacy can have a significant effect on students' academic achievement and progress of educational system. The aim of this study is to investigate the effects of the Snyder's theory-based group hope therapy on academic self-efficacy beliefs and hope in freshman students. In total, 45 freshman students were recruited and randomly assigned to two groups: intervention g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 45 publications
1
6
0
Order By: Relevance
“…The results showed that group hope therapy based on Snyder's theory has a significant effect on self-efficacy of the adolescents with T1D. This finding was consistent with the results of previous studies [7][8][9][10][11] .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The results showed that group hope therapy based on Snyder's theory has a significant effect on self-efficacy of the adolescents with T1D. This finding was consistent with the results of previous studies [7][8][9][10][11] .…”
Section: Discussionsupporting
confidence: 91%
“…During hope therapy and after setting a goal, people look for ways to achieve the goal by assessing obstacles and barriers and thinking about ways to overcome them. This helps individuals find their abilities and motivations, in which indirectly makes them confident and increases their self-efficacy 11 . However, the results of the present study are not in line with the study conducted by Moayed et al Although hope therapy training in their study increased self-efficacy, its effect was not significant 13 .…”
Section: Discussionmentioning
confidence: 99%
“…Hope has been identified as a psychological factor that contributes to self-reported health and well-being, improvement in health adjustment, with a positive relationship to quality of life (Billington et al, 2008;Lazarus, 1999;Perveen, 2019;Scioli et al, 2016;Tian et al, 2018). Snyder and colleagues defined hope as, 'a cognitive set that is based on a reciprocally derived sense of agency and pathways' (Snyder et al, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…Hopelessness is among the most important factors predicting depression especially among the elderly (6,7). Hopelessness is also a feature of depression during which the person feels incompetent and worthless (8)(9)(10). It negatively affects the feeling of functionality, selfesteem, suitable interaction with others, achieving life goals and finally, leads to depression (2,11,12).…”
Section: Introductionmentioning
confidence: 99%
“…Research indicated that mindfulness led to decrease of psychological distress and anxiety symptoms (20) and improvement of mental, physical, emotional, spiritual and self-efficacy welfare (21). Moreover, it decreases depression symptoms of the elderly females (9,10). On the other hand, studies demonstrated that compassion-based therapy is effective on the ability to tolerate ambiguity and death' anxiety (22); hence, it can be said that mindfulness-based compassion therapy plays a key role on decrease of hopelessness and rumination among the elderly while the issue was not much considered in previous studies.…”
Section: Introductionmentioning
confidence: 99%